Weight loss methods and diet history among bariatric surgery candidates - Vertiz, Lizbeth Guilbert; Sahagún, César Manuel Vargas; Guerrero, Elisa Maria Sepúlveda; Licona, Carmen Georgina Castelán; Escobedo, Sergio Ulises Pérez; Zerrweck, Carlos (International Journal of Research in Medical Sciences, 2022)
Background: Nowadays there are multiple conservative treatments, medical and alternative for weight loss, with high failure levels in patients with obesity. The history of variability, effectiveness, and diversity of such treatments has been poorly explored in candidates to bariatric surgery, particularly in Latin America, where high rates of overweight and obesity are found. Methods: Cross-sectional study in a single center, where a questionnaire was given to all patients who presented for bariatric surgery evaluation. The primary objective was to identify the dietary history and methods used for weight loss in patients with obesity, focusing in the diet type/method, length, effectiveness, and weight regain. Also, a basal anthropometric/demographic analysis, and type of method used (diet, medications, homeopathy, supplements, and alternative therapies) was performed. Results: 400 questionnaires were evaluated, from which the average age was 40.2 years, 79.5% representing female sex, and an average weight of 114.8 kg. Childhood obesity was reported in 38%. 64.5% used among 1-5 methods to lose weight historically, but 74.7% never associated physical activity. Supervised diet (with and without medication) was the most effective method (44% of cases used medication); however, they were discontinued in 50.5% due to adverse effects. Conclusions: The use of a diet or alternative treatments, with or without medications, have shown poor weight loss and minimum durability. The use of medication is very common, but most people discontinue their use due to adverse effects events.